2011
DOI: 10.1007/s10620-011-1777-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characteristics of Distension-Evoked Peristaltic Contractions in the Esophagus of Systemic Sclerosis Patients

Abstract: Distension-evoked esophageal contraction can be studied in vivo and analyzed with advanced methods. Increased esophageal stiffness and impaired muscle function that depended on disease duration were observed for SS patients. The analysis may be useful for characterization of other diseases affecting GI function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 24 publications
2
33
1
Order By: Relevance
“…Thus, greater the duration of the disease, the greater is the binding accounting for the progressive nature of GIT involvement in SSc. Similar results were shown in a study wherein esophageal stiffness and impaired muscle function on manometry correlated with disease duration (12).…”
Section: Discussionsupporting
confidence: 87%
“…Thus, greater the duration of the disease, the greater is the binding accounting for the progressive nature of GIT involvement in SSc. Similar results were shown in a study wherein esophageal stiffness and impaired muscle function on manometry correlated with disease duration (12).…”
Section: Discussionsupporting
confidence: 87%
“…The combined impedance planimetry and manometry technology with measurement of pressure–cross‐sectional area (P–CSA) relations of the distending bag provides the needed data in vivo for force–deformation analysis in the esophagus . In our recent studies, we made a first attempt of applying P–CSA recordings to study the mechanical energy output of esophageal secondary peristaltic contractions in healthy volunteers and in patients with systemic sclerosis (SS) . In a recent study done using cardiac pump function analysis, we found that SS patients had different P–CSA loop shapes with smaller work output.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, tension–stretch ratio loops in patients with systemic sclerosis were shifted to the left, indicative of a stiffer wall in patients. Lower contraction amplitudes and smaller P‐CSA loops resulted in lower work output, power output, Δ tension, and contraction velocity for the patients compared to healthy subjects . These studies clearly demonstrated the usefulness of loop analysis. Force–velocity and force–power relations have been demonstrated in the normal and diseased esophagus.…”
Section: Application Of Cardiac Muscle Concepts To the Esophagusmentioning
confidence: 53%